Predisposing, Enabling, and Need Factors Associated with the Choice of Pharmacy Type in the US: Findings from the 2015/2016 National Consumer Survey on the Medication Experience and Pharmacists' Roles - Mohamed Rashrash; Suhila Sawesi; Jon C. Schommer; Lawrence M. Brown (MDPI AG, 2021)
Background: Knowing the type of pharmacy used by the patient is meaningful to the pharmacist. Previous studies have assessed different factors predicting the kind of pharmacy selection and reached inconsistent findings. Objectives: To identify patient and health-related factors associated with pharmacy type selection. Methods: The Andersen Behavioral Model of Health Service Use was used to organize the selection of patient characteristics and categorize them as predisposing, enabling, and need factors. The dependent variable was the type of pharmacy used. Logistic regression was used to predict the association between patient-related characteristics and the type of pharmacy used. Results: Older age respondents were less likely to use independent pharmacies (OR = 0.992) and more likely to use mail pharmacy services (OR = 1.026). Highly educated people showed higher use of chain and mail pharmacies (OR = 1.272, 1.185, respectively) and less tendency to use the independent, supermarket, and prescription-only pharmacy types. Men were less likely to use chain pharmacies (OR = 0.932) and more likely to use supermarket pharmacies than women. Patients who use Medication Therapy Management (MTM) services had higher odds of using independent and supermarket pharmacies (OR = 2.808, 1.689, respectively). Patients with a higher number of chronic diseases and experienced side effects of medications were more likely to use independent pharmacies (OR for number of disease = 1.097 and for side effects = 1.095). Conclusions: This study's findings identify characteristics associated with selecting certain pharmacy settings and direct future research to include other predictors encompassing beliefs, attitudes, and other social factors.